The Role of Innovation Using ICT in Mediating Learning Management and Performance to Improve Educational Quality at SMK Negeri 1 Pemalang - Atminah, Sri; Utanto, Yuli (Universitas Negeri Semarang, 2025)
The research is based on the less than optimal learning and performance management system that causes low quality of education. The purpose of the study is to examine the influence of learning and performance management on the quality of education through innovation using ICT as a mediating variable. The population is teachers of SMK Negeri 1 Pemalang, sampling with stratified random sampling technique. From the Slovin formula obtained 55 respondents. Data collection method with questionnaires. Data analysis technique with path analysis, significance 5%. The results of the study: learning management has a positive and significant effect on the quality of education 69.0%. Performance management has a positive and significant effect on the quality of education 47.7%. Sobel Test Results: through mediation using ICT, learning management has a positive and significant effect on the quality of education 81.4% and performance management has a positive and significant effect on the quality of education 84.2%. Conclusion: learning and performance management has a positive and significant direct effect on the quality of education, the mediating role of innovation using ICT can increase the positive influence of learning and performance management on the quality of education